The genus Stilbocoris in the Malagasy area (Hemiptera: Heteroptera: Rhyparochromidae) - Kondorosy, Előd; Zámbó, András (Zootaxa, 2021)
The species of Stilbocoris Bergroth, 1893 (Hemiptera: Heteroptera: Rhyparochromidae: Rhyparochrominae: Drymini) occurring in Madagascar and surrounding islands are reviewed. Four described and two undescribed species (S. scudderi sp. nov. and S. slateri sp. nov.) are recognized, the latter two apparently being endemic to Madagascar. The following new country records are provided: S. distinctus Scudder, 1962: Ivory Coast, Ghana, Togo, Central African Republic, Gabon, Cameroon and Madagascar; S. galla Linnavuori, 1978: Kenya, Tanzania and Madagascar; S. triangularis Linnavuori, 1978: Senegal, Tanzania and Madagascar. A key for the species occurring in the Malagasy area is presented.